Does being a leader make them stay? Short- and long-term effects of supervisory responsibility on turnover intentions - Stephanie Funk (Human Resource Management Journal, 2024)
Employers want to avoid fluctuation, especially when qualified personnel is involved. This raises the question of whether promoting employees into leadership positions with supervisory responsibility helps to retain them. Based on social exchange theory, this article predicts that in the short run, employees have lower turnover intentions due to reciprocal feelings. In the long run, following human capital theory, supervisory responsibility increases an employee's turnover intentions due to the general skills acquired in the leadership position. This article argues that human resource management (HRM) practices that enhance an individual's internal career development counteract this long-term turnover-increasing effect by offering employees internal advancement opportunities. This study empirically tests these predictions using German linked employer-employee data. The results support the predicted short-term turnover-reducing and the long-term turnover-increasing effect of supervisory responsibility. The results also reveal that for long-term supervisors appraisal interviews and development plans, two examples of HRM practices, counteract the effect by reducing an employee's intention to quit.
Keywords: 650; human resource management practices; leadership; retention; supervisory responsibility; turnover intentions